Comparison of noradrenaline, dopamine and serotonin in mediating the tachycardic and thermogenic effects of methamphetamine in the ventral medial prefrontal cortex. (4th June 2015) - Hassan, S.F.; Zumut, S.; Burke, P.G.; McMullan, S.; Cornish, J.L.; Goodchild, A.K.
Highlights: NA in the ventral mPFC drives cardiac, respiratory and metabolic outflows in a dose-related manner. High-dose METH in the ventral mPFC evokes thermogenesis and tachycardia. Low-dose METH and DA in the ventral mPFC have little effect except to possibly reduce respiration. NA and 5-HT in the ventral mPFC have opposing hemodynamic effects. Abstract: Methamphetamine (METH) is a psychostimulant that disrupts monoaminergic neurotransmission to evoke profound behavioral and physiological effects. Rapidly distributing to forebrain regions to increase synaptic concentrations of three monoamines (dopamine (DA), serotonin (5-HT) and noradrenaline (NA)), the medial prefrontal cortex (mPFC) is important in METH-altered behavioral and psychological profiles. Activation of the ventral mPFC can modify physiological variables, however, METH-evoked autonomic changes from this region are unknown. Therefore, the aim of this study was to characterize the respiratory, metabolic and cardiovascular effects of microinjection of METH, DA, 5-HT and NA into the ventral mPFC in urethane-anesthetized Sprague–Dawley rats. METH and NA microinjection evoked dose-related increases in heart rate, interscapular brown adipose tissue temperature and expired CO2, a pattern of response characteristic of non-shivering thermogenesis. NA and 5-HT microinjection elicited pressor and depressor responses, respectively, with matching baroreflex adjustments in sympathetic nerve activity while METH and DA evoked no change in vasomotor outflow. Low doses of METH and DA may evoke respiratory depression. These data suggest that METH's actions in the ventral mPFC, likely via adrenergic receptors, evoke non-shivering thermogenesis which may contribute to the increased body temperature and tachycardia seen in those that abuse METH.